Exploring directly the neural correlates of feedback-related reward saliency during fMRI-based Neurofeedback - Ramos, Manuel Coelho Moura (2019)
Dissertação de Mestrado Integrado em Engenharia Biomédica apresentada à Faculdade de Ciências e Tecnologia